Speak beyond the edge: Chinese and American confessional poetry in a cross-cultural context - Zhang, Xiaohong; Chen, Xiaomin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
American confessional poetry surfaced on the literary horizon against the backdrop of the time-honored Western confessional tradition and a clamorous post-War American society . As an experimental poetic voice, it challenged the yokes of all kinds: political, military, moral, cultural and literary . In the 1980s, warm reception of American confessional poetry in China engendered a discourse of Chinese confessions that is markedly poignant, dark and introspective.
Keywords: confessional poetry; reception; politics; women poets; gender politics